The Basics and Significance of Auxiliary Verbs in Modern Mongolia : Орчин цагийн монгол хэлний туслах үйл үгийн үндэслэл, ач холбогдол - Бён Гү, Сон (Acta Mongolica, 2008)
In this article the author deals with the basic notion and significance of auxiliary verbs in Modem Mongolian in more details. A special study on what should be the causes for auxiliaries to be called so is been actually absent among previous researchers. Since the detailed observation on their peculiarities and significance are in lack a special attention was paid to this aspect and they were considered in six ways. There should be some more peculiarities apart from these six. In this case they are supposed to be specified in the future researches, as the author claims. The researches should present more interest if it is conducted in comparison of the Mongolian language with the other relative languages of the same group.